The Role of Board Gender Diversity, Age Diversity, and Foreign Experience on CSR - Utami, Devi Wahyu; Doddy Setiawan (Universitas Tidar, 2024)
This research aims to provide empirical evidence regarding the role of board gender diversity, age diversity and foreign experience on corporate social responsibility (CSR). This research was conducted on property and real estate sector companies listed on the Indonesia Stock Exchange 2018-2022. The research sample obtained 210 observations taken through purposive sampling. Data analysis was carried out using regression analysis with Stata software. The research results prove that board gender diversity has a negative influence on CSR, age diversity has a positive influence on CSR and foreign experience has an influence on CSR.